Anaphylaxis triggered by prick test with latex extract: a case report - Mendonça, Leonardo Oliveira; Lima, Cynthia Mafra Fonseca de; Macedo, Priscilla Rios Cordeiro; Cunha, Victor do Espirito Santo; Hahnstadt, Ruppert Ludwig; Kalil, Jorge; Galvão, Clóvis Eduardo Santos (São Paulo Medical Journal, 2019)
CONTEXT: Adverse reactions associated with prick tests are rare but may be present as serious systemic reactions. CASE REPORT: A 38-year-old female nursing technician complained of three episodes of anaphylaxis in one year, all in the workplace. To investigate latex allergy, the patient underwent the prick test with latex, and immediately developed a rash, itchy skin, hoarseness, dyspnea and dry cough. Her condition im-proved promptly after appropriate measures were established for controlling her anaphylaxis. CONCLUSION: The skin test must be performed under medical supervision, since complications that can lead to life-threatening reactions, if support measures are not readily implemented, have been attributed to this test.